The Standardization of growing substrate for multiplication of guava (Psidium guajava) through cuttings - SHEIKH, TALIB AFZAL; MUKHTAR, YOUSRA; JASROTIA, AMIT; BAKSHI, PARSHANT (The Indian Journal of Agricultural Sciences, 2023)
Experiments under the polyhouse were conducted for two consecutive years (2021 and 2022) at Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu (SKUAST-J), Jammu and Kashmir to evaluate the effect of different growing substrates on guava (Psidium guajava L.) multiplication through cuttings. Twelve substrate combinations were tried in polybags and polytrays under a polytunnel in a polyhouse provided with mist irrigation. The study revealed a positive effect of different growing substrates on growth parameters and successful propagation of guava cuttings. The perusal of the pooled data revealed that T9 was the most effective growing substrate which recorded maximum rooting percentage, survival percentage, plant height, fresh and dry weight, the diameter of thickest sprout, shoot length, length of longest root, leaf area, and the number of roots, shoots, leaves per longest shoot along with minimum mortality percentage and days to first sprouting. However, some growth parameters such as stem thickness, chlorophyll percentage, number of sprouts, sprouted cuttings, and leaves of planted guava cuttings yielded the best results in T10. Cuttings grown in topsoil only without any growing substrate (T12) provided the least values of all the growth parameters of guava cuttings.